INSTRUCTIONAL LEADERSHIP, JOB SATISFACTION, COMMITMENT, AND TEACHER PERFORMANCE IN NORTH BANJARMASIN - Ita Rahmiyani; Ahmad Suriansyah; Aslamiah Aslamiah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the direct and indirect relationships between principals’ instructional leadership, job satisfaction, work commitment, and teacher performance in public elementary schools in North Banjarmasin District, Banjarmasin City. The research employed a cross-sectional design using a path analysis model to examine the relationships among variables. The population consisted of 309 teachers from 27 public elementary schools in the district. Using the probability simple random sampling technique, 174 teachers were selected as research respondents. Data were collected through questionnaires and analyzed using descriptive statistics, classical assumption tests, hypothesis testing, and path analysis. The results indicate that all research variables are categorized as high. The regression coefficient values show strong relationships among variables, including instructional leadership and teacher performance (0.825), job satisfaction and teacher performance (0.829), work commitment and teacher performance (0.816), instructional leadership and work commitment (0.783), and job satisfaction and work commitment (0.486). The analysis also reveals indirect relationships, where instructional leadership influences teacher performance through work commitment (0.337) and job satisfaction affects teacher performance through work commitment (0.3691). These findings demonstrate that principals’ instructional leadership, teachers’ job satisfaction, and work commitment significantly contribute to improving teacher performance, both directly and indirectly. The study suggests that school principals should continue strengthening instructional leadership practices, particularly by enhancing interaction with teachers and providing opportunities for professional development and training. Meanwhile, teachers are encouraged to continuously improve their performance by applying effective teaching strategies and comprehensive assessment methods that evaluate not only students’ cognitive achievements but also their behavioral and moral development, supporting overall student success in the contemporary learning environment.